Features and catalytic properties of RhCu: A review - Illas, F. (2009)
The study of bimetallic catalysts has scientific and technologic importance because of special catalytic activity towards several reactions. RhCu is an interesting bimetallic system due to combination of the very different catalytic activities of Rh and Cu. The catalytic activity of this bimetallic does not result from simple interpolation of the constituents. In fact, at low Cu content, the catalytic activity of RhCu is superior to that of Rh but when the Cu content is higher the activity decays. This is a curious trend which theoretical works had attempted to explain. This paper reports an overview of the most recent research works about this bimetallic system with emphasis in its especial characteristics.